EFEKTIVITAS SANKSI HUKUM ADAT DI DESA BINANGGA KECAMATAN MARAWOLA KABUPATEN SIGI - Tahali, Ahmad; Munarif; Sauki Alhabsyi, Muhamad; Atma R. Massi, Randy; Ananda Almahdali, Atika (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
The application of customary law sanctions in Binangga Village plays a significant role in maintaining social harmony and resolving conflicts through a restorative approach aimed at improving relations between residents and emphasizing the importance of customary norms. Conflict resolution mechanisms that prioritize deliberation and involve traditional leaders as mediators make customary law more accepted by the community. Factors supporting its effectiveness include the level of community compliance with cultural values, the role of respected traditional leaders, and a restorative approach. However, challenges such as modernization, globalization, internal conflicts, and differences with national laws are obstacles. Therefore, synergy between indigenous peoples, government and national law is needed to maintain the relevance and effectiveness of customary law in the face of continuously developing social dynamics.